Rapid generation of functional hepatocyte-like cells from human adipose-derived stem cells. Issue 1 (December 2016) - Fu, Yanli; Deng, Jie; Jiang, Qingyuan; Wang, Yuan; Zhang, Yujing; Yao, Yunqi; Cheng, Fuyi; Chen, Xiaolei; Xu, Fen; Huang, Meijuan; Yang, Yang; Zhang, Shuang; et al.
Abstract Background Liver disease is a major cause of death worldwide. Orthotropic liver transplantation (OLT) represents the only effective treatment for patients with liver failure, but the increasing demand for organs is unfortunately so great that its application is limited. Hepatocyte transplantation is a promising alternative to OLT for the treatment of some liver-based metabolic disorders or acute liver failure. Unfortunately, the lack of donor livers also makes it difficult to obtain enough viable hepatocytes for hepatocyte-based therapies. Currently, a fundamental solution to this key problem is still lacking. Here we show a novel non-transgenic protocol that facilitates the rapid generation of functional induced hepatocytes (iHeps) from human adipose-derived stem cells (hADSCs), providing a source of available cells for autologous hepatocytes to treat liver disease. Methods We used collagenase digestion to isolate hADSCs. The surface marker was detected by flow cytometry. The multipotential differentiation potency was detected by induction into adipocytes, osteocytes, and chondrocytes. Passage 3–7 hADSCs were induced into iHeps using an induction culture system composed of small molecule compounds and cell factors. Results Primary cultured hADSCs presented a fusiform or polygon appearance that became fibroblast-like after passage 3. More than 95 % of the cells expressed the mesenchymal cell markers CD29, CD44, CD166, CD105, and CD90. hADSCs possessed multipotential differentiation towards adipocytes, osteocytes, and chondrocytes. We rapidly induced hADSCs into iHeps within 10 days in vitro; the cellular morphology changed from fusiform to close-connected cubiform, which was similar to hepatocytes. After induction, most of the iHeps co-expressed albumin and alpha-1 antitrypsin; they also expressed mature hepatocyte special genes and achieved the basic functions of hepatocyte. Moreover, iHep transplantation could improve the liver function of acute liver-injured NPG mice and prolong life. Conclusions We isolated highly purified hADSCs and rapidly induced them into functional hepatocyte-like cells within 10 days. These results provide a source of available cells for autologous hepatocytes to treat liver disease.